Sistema interativo de apoio ao aprendizado para projeto geométrico de vias - Garcia, Dorotéa Vilanova (2004)
This work has as objective to develop an interactive ambient that uses a computer, conceived to aid the geometric project of wheelwork highways, considering that educational softwares in the teaching-learning atmosphere has been more and more frequent in all the levels of the education. This way, it was made a research, involving the concepts of the learning process, that is, the educational paradigms, ergonomics of man/machine interface and its pedagogic involvement. A target public, the course of Civil Engineering, was chosen with the purpose of elaborating the calculations involved in the geometric project of highways, and the coalition of those information converged for the interactive system elaboration, generating a rich source of knowledge. The focus of this work is centered in two properties: usability (with an ergonomic character) and learning (with a pedagogic character), facilitating the learning of the system, as well as the learning in the system. So a simulator was conceived to work in agreement with the instructional modules, indicating that there is integration of the approaches of larger conformity in usability and the learning approaches, which are defined to validate the pedagogic quality of the software. The process teaching-learning should prioritize the students' learning on the form of the teachers’ teaching, because the student is the focus of educational institution. This way, the use of softwares of this nature can aid the development of critical thinking and the learning to learn process, contributing for dealing with intellectuals purposes with would be difficultly possible in there best forms without the use of the computer.